Online Voltage Sensorless High-Resistance Connection Diagnosis in Induction Motor Drives - de la Barrera, Pablo Martin (2015)
A new method for online high-resistance connection (HRC) diagnosis in induction motor (IM) drives is presented in this effort. This voltage sensorless method is based on a signal injection strategy applied to the IM during its normal operation. The signal is injected in the d-axis in such a way that it provides the phase currents with a dc component while avoiding torque perturbation. By measuring phase currents, it is possible to detect and isolate HRC problems. Experimental results showing high sensitivity to HRCs and immunity to symmetrical stator resistance variations have been obtained in a laboratory setup. The low perturbation produced by the injection method over the IM variables has also been experimentally demonstrated.